Synthesis of Rh-carbon nanotube based heterostructures and their enhanced field emission characteristics - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Chemical Communications, 2010)
Selective decoration of Rh nanospheres on acid functionalized carbon nanotubes has been demonstrated using Al as a sacrificial substrate. Remarkable field emission has been observed for this heterostructure as a high current density of 170 mu A cm(-2) is generated at an ultra-low threshold of 300 V mu m(-1), compared to much smaller values for Rh nanospheres and carbon nanotubes separately.